1988
DOI: 10.1111/j.1476-5381.1988.tb11414.x
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of airway epithelium in modulating hyperresponsiveness

Abstract: 1In order to examine the role of airway epithelium in the responsiveness of smooth muscle in man, we measured the contractile responses to acetylcholine (ACh), histamine, and prostaglandin F2, (PGF2,) and the relaxation response to isoprenaline (Isop), in 48 bronchi obtained from 10 patients who received surgery. Responses were measured in the presence and absence of the epithelium. 2 Removal of epithelium (by rubbing the mucosa gently with forceps) significantly increased the contractile responses evoked by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…It is now well established in vitro that the epithelium has a significant role to play in modulating airway smooth muscle responsiveness to spasmogenic and relaxant agonists in several species including man (Barnes et al, 1985;Flavahan et al, 1985;Goldie et al, 1986;Raeburn et al, 1986;Aizawa et al, 1988;Vanhoutte, 1988). It has been suggested that the airway epithelium may secrete an inhibitory factor which can modulate airway smooth muscle responsiveness to various agonists (Flavahan et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established in vitro that the epithelium has a significant role to play in modulating airway smooth muscle responsiveness to spasmogenic and relaxant agonists in several species including man (Barnes et al, 1985;Flavahan et al, 1985;Goldie et al, 1986;Raeburn et al, 1986;Aizawa et al, 1988;Vanhoutte, 1988). It has been suggested that the airway epithelium may secrete an inhibitory factor which can modulate airway smooth muscle responsiveness to various agonists (Flavahan et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have shown that the sensitivity of airway smooth muscle preparations from various animal species (Barnes et al, 1985;Flavahan et al, 1985;Goldie et al, 1986;Hay et al, 1986) including man Aizawa et al, 1988;Knight et al, 1990) to several bronchoconstrictor agents is significantly increased by removal of the epithelium. These studies have led to the hypothesis that the epithelium can release an inhibitory factor(s) other than prostaglandins (designated as epithelium-derived inhibitory or relaxing factor, EpDIF/ EpDRF; Farmer, 1988;Fedan et al, 1988;Vanhoutte, 1988;Goldie et al, 1990;Raeburn, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this comes from the observation that mechanical removal of epithelium increases the sensitivity to a variety of spasmogens of isolated airway smooth muscle from both animals (Goldie, Fernandes, Farmer & Hay, 1990) and humans (Raeburn, Hay, Farmer & Fedan, 1986;Aizawa, Miyazaki, Shigematsu & Tomooka, 1988;Fernandes et al 1989Fernandes et al , 1990. More direct evidence for the release of an epithelium-derived inhibitory factor (EpDIF) has been provided by the coaxial bioassay, consisting of an assay preparation mounted within the lumen of an airway tube segment, which was first described by Ilhan & Sahin (1986).…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few reports on human airway epithelium (Raeburn et al 1986;Aizawa et al 1988;Fernandes et al 1989Fernandes et al , 1990 …”
Section: Discussionmentioning
confidence: 99%